Role of in-situ simulation for training in healthcare: opportunities and challenges. Issue 6 (December 2017) - Kurup, Viji; Matei, Veronica; Ray, Jessica
Abstract : Purpose of review: Simulation has now been acknowledged as an important part of training in healthcare, and most academic hospitals have a dedicated simulation center. In-situ simulation occurs in patient care units with scenarios involving healthcare professionals in their actual working environment. The purpose of this review is to describe the process of putting together the components of in-situ simulation for training programs and to review outcomes studied, and challenges with this approach. Recent findings: In-situ simulation has been used to 'test-drive' new centers, train personnel in new procedures in existing centers, for recertification training and to uncover latent threats in clinical care areas. It has also emerged as an attractive alternative to traditional simulations for institutions that do not have their own simulation center. Summary: In-situ simulation can be used to improve reliability and safety especially in areas of high risk, and in high-stress environments. It is also a reasonable and attractive alternative for programs that want to conduct interdisciplinary simulations for their trainees and faculty, and for those who do not have access to a fully functional simulation center. Further research needs to be done in assessing effectiveness of training using this method and the effect of such training on clinical outcomes.